Hostile Geographies: Black Girls Fight to Save Themselves and the World. Issue 1 (1st March 2022) - Rogers, Dehanza
Abstract: In this article, I engage in a parallel reading of the consumption of Black girlhood in speculative fiction in the television series The Passage, and the film The Girl with All the Gifts, and in the classroom. In these texts are nonconsensual attempts to harvest biological materials from Black girls, exhibiting the belief that Black bodies are utilitarian, at best, and meant for consumption. Like these narratives, the classroom consumes Black girls physically along with their futures. I explore how Black girl resistance disrupts such consumption and interrogate texts in which Black girls create narratives for themselves. In these narratives, so-called disposable Black girls map out new cartographies of narrative resistance and new liberatory geographies for their future.